EFFECTS OF THE FISIOLOGIC AGE OF SOYBEAN SEEDS IN THE RESULTS OF THE TEST OF ACCELERATED AGING. - Aranha, Maria Teresa M.; Lamas, Fernando M.; Ferreira, Lino R.; Carvalho, Nelson M.; Oliveira, Antonio L. (Revista de Ciências Agroveterinárias, 2002)
With the objective to study the effect of the fisiologic age of soybean seeds in the results of the test of accelerated aging, it was lead en the laboratory of the Department of Fitotecnia of FCAVJ/ UNESP, an experiment with soybean seeds, CV. IAC 8 proceeding from harvests 1992/93, 93/94 and 94/95. Five periods has been used of stress (36, 48, 60, 72 and 84 hours). The analysed variables had been percentage of germination in the fifth day and the index of emergency speed. A complete randomized experimental design, with a factorial arrangement, was used. For the seeds of harvest 1992/93, that initially they presented germination of 68%, the aging after 48 hours was enough to reduce in 58% its germination. For harvests 93/94 and 94/95, with initial germination of 96 and 98,5%, respectively, the time of aging to reduce in 50% the germination was not detected, with up to 84 hours of estresse. The results indicate that the period of aging to be used in soybeans, must consider the initial quality of the seeds.